Individual variability in behavioral flexibility predicts sign-tracking tendency - Nasser, Helen M.; Chen, Yu-Wei; Fiscella, Kimberly; Calu, Donna J. (Frontiers in Behavioral Neuroscience, 2015)
Sign-tracking rats show heightened sensitivity to food- and drug-associated cues, which serve as strong incentives for driving reward seeking. We hypothesized that this enhanced incentive drive is accompanied by an inflexibility when incentive value changes. To examine this we tested rats in Pavlovian outcome devaluation or second-order conditioning prior to the assessment of sign-tracking tendency. To assess behavioral flexibility we trained rats to associate a light with a food outcome. After the food was devalued by pairing with illness, we measured conditioned responding to the light during an outcome devaluation probe test. The level of conditioned responding during outcome devaluation probe test correlated with the rats’ subsequent tracking tendency, with sign-tracking rats failing to suppress conditioned responding to the light after outcome devaluation. To assess Pavlovian incentive learning, we trained rats on first-order (CS+, CS-) and second-order (SOCS+, SOCS-) discriminations. After second-order conditioning, we measured conditioned responding to the second-order cues during a probe test. Second-order conditioning was observed in all rats regardless of tracking tendency. The behavioral inflexibility of sign-trackers has potential relevance for understanding individual variation in vulnerability to drug addiction.